A3_3 This Time Next Year, We'll be Millionaires! - Cooper, Dan; Reiness, Sean; Sidhu, Manika Kaur; Watson, Charlie (Physics Special Topics, 2017)
The path to ‘getting rich quick’ is one fraught with instability and conjecture. In the British sitcom Only Fools and Horses, stock marketer Del Boy Trotter notoriously claims that “This time next year, we’ll be millionaires”. In this article we utilise the special relativistic phenomenon that is time dilation to calculate the conditions under which this feat would be possible. We found that by investing $3000 in three companies in the 1980s, travelling at 0.999c for 12 ly and instantaneously turning around to undergo a return journey, Del Boy Trotter could have become a millionaire in only a year.